"He was no longer listening to me": A qualitative study in six Sub-Saharan African countries exploring next-of-kin perspectives on caring following the death of a relative from AIDS. Issue 6 (3rd June 2019) - Ssekubugu, Robert; Renju, Jenny; Zaba, Basia; Seeley, Janet; Bukenya, Dominic; Ddaaki, William; Moshabela, Mosa; Wamoyi, Joyce; McLean, Estelle; Ondenge, Kenneth; Skovdal, Morten; Wringe, Alison
ABSTRACT: In the era of widespread antiretroviral therapy, few studies have explored the perspectives of the relatives involved in caring for people living with HIV (PLHIV) during periods of ill-health leading up to their demise. In this analysis, we explore the process of care for PLHIV as their death approached, from their relatives' perspective. We apply Tronto's care ethics framework that distinguishes between care-receiving among PLHIV on the one hand, and caring about, caring for and care-giving by their relatives on the other. We draw on 44 in-depth interviews conducted with caregivers following the death of their relatives, in seven rural settings in Eastern and Southern Africa. Relatives suggested that prior to the onset of poor health, few of the deceased had disclosed their HIV status and fewer still were relying on anyone for help. This lack of disclosure meant that some caregivers spoke of enduring a long period of worry, and feelings of helplessness as they were unable to translate their concern and "caring about" into "caring for". This transition often occurred when the deceased became in need of physical, emotional or financial care. The responsibility was often culturally prescribed, rarely questioned and usually fell to women. The move to "care-giving" was characterised by physical acts of providing care for their relative, which lasted until death. Tronto's conceptualisation of caring relationships highlights how the burden of caring often intensifies as family members' caring evolves from "caring about", to "caring for", and eventually to "giving care" to their relatives. This progression can lead to caregivers experiencing frustration, provoking tensions with their relatives and highlighting the need for interventions to support family members caring for PLHIV. Interventions should also encourage PLHIV to disclose their HIV status and seek early access to HIV care and treatment services.